Pelaksanaan Penilaian Autentik Kurikulum 2013 pada Mata Pelajaran PAI di SMP PAB 8 Sampali - Neliwati, Neliwati; Nisa, Suliatun; Arleni, Rizky Nanda; Sinembela, Rasyidi (MODELING: Jurnal Program Studi PGMI, 2023)
Planning, implementing, and evaluating it is part of the learning process. One tool to assess the extent to which the planned learning objectives have been met is an assessment. Authentic assessment is one of the evaluations used in education. Tests that combine learning processes and objectives are called authentic assessments. The purpose of this study was to provide an overview of the use of authentic assessment in the Islamic Religious Education subject at SMP PAB 8 Sampali as evidenced by the use of authentic assessment on the elements of attitude, knowledge and skills. This research is qualitative with a descriptive approach. Data collection in this study was carried out using interview techniques, field observations (observations), and collection, as well as using data collection techniques in the form of library research. The subjects in this study were teachers of Islamic Religious Education at SMP PAB 8 Sampali. The results of the research that the researchers conducted at SMP PAB 8 Sampali, namely that even though it was not fully in accordance with the assessment guidelines, authentic assessments had been carried out.